Copley Square Hotel at 49 Huntington Avenue, ca. 1959 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-northeast of the Copley Square Hotel, located at 49 Huntington Avenue. The south-southwest elevation of the hotel faces Exeter Street, visible in the center of the photograph. Automobiles are parked along Exeter Street and in the railroad yard parking lot located between Huntington Avenue to the south-southeast and Boylston Street to the north-northwest. Portions of two railroad cars and several barrels are included in the lower-left half of the photograph. Electricity lines and pedestrians are also included in the photograph. 7 3/4 x 7 7/16, 9 7/8 x 8 overall Photographs